DIFFERENT APPROACHES TO EXPRESSING LOVE FOR THE MOTHERLAND IN ENGLISH AND UZBEK POETRY - Qurbonova Nodira Roziqovna; Karimova Dilshoda (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the work of poets in praise of the motherland in English and Uzbek poetry of the 20th century is studied. Also, the poems of poets of two nationalities are comparatively analyzed and the different views on describing the motherland are explained.